ACOUSTO-EMISSION EXPRESS-CONTROL OF HYDROGEN CONTENTS IN LIQUID ALUMINIUM AND ITS ALLOYS - V. B. Vorontsov; A. V. Gorchinski (Литьë и металлургия)
Thе methods and outfit Angara-P, allowing to determine the contents of hydrogen in liquid aluminium and aluminium alloys in range 0,05-5,0 cm3/100g of melt accurate within + 0,03 - 0,08 cm3/100g, are developed. AE-method gives possibility to carry out analysis during 1,0—1,5 min.